SCANTURF ‐ Evaluation of turfgrass varieties for lawns and sports grounds in Scandinavia. Issue 1 (24th February 2021) - Havstad, Lars T.; Niskanen, Markku; Larsen, Anders S.; Aamlid, Trygve S.
Abstract: SCANTURF is a joint Nordic programme for turfgrass variety testing, set up in 2005 and funded by variety entrance fees only. It replaced and simplified the former government‐funded national evaluation programmes in Finland, Sweden, Denmark and Norway. The programme includes testing of all cool‐season grasses on lawn/fairways at 15–20 mm mowing height ("lawn trials") and optional testing of Poa pratensis L. and Lolium perenne L. on simulated football pitches with wear, mowed at 30 mm ("wear trials"). Since 2013, the program has regarded the Nordic countries as one trial zone with three test sites: Tystofte Denmark (55°15′ N, 11°20′ E), Landvik, Norway (58°21' N, 8°32' E) and Ylistaro, Finland (62°57′ N, 22°31' E). Wear trials are carried out at the intermediate location Landvik only. Candidate varieties are tested against two reference varieties of the same species or subspecies. In the lawn trials, candidate varieties are evaluated for visual merit (overall turfgrass quality), winter damage, winter color, diseases and daily height growth at all three locations and for tiller density, fineness of leaves, in‐season (genetic) color, at Landvik only. Based on the results from the SCANTURF trials in 2014–2016 and 2016–2018, the candidate varieties Fabian, Tetrastar, Annecy, and Monroe ( Lolium perenne ), Becca, Harmonie, Traction, and Markus ( Poa pratensis ) and Lystig, Greenmile, and Humboldt ( Festuca rubra ssp. commutata ) were recommended for lawns in the Nordic countries, while Eurocordus, Columbine, Monroe, and Annecy ( Lolium perenne ) and Harmonie ( Poa pratensis ) were recommended for sports grounds. More use of the recommended varieties will have a positive effect on quality of lawns and sport grounds in the Nordic countries. Less winter injury and increasing relative performance with increasing latitude of the tetraploid perennial ryegrass variety Fabian in the lawn trials may possibly lead to more use of perennial ryegrass in the northern and more continental parts of the region.